The Use of Gerunds and Reported Speech in Academic and Informal Texts - Anas Nst, Syarifah; Pasaribu, Nur Saniyah; Irhamuddin, Irhamuddin; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study aims to examine the use of gerund and reported speech in academic and nonformal texts, as well as to identify common errors in their usage. Using a literature review approach, data were analyzed from various sources such as academic journals, grammar books, and related research articles. The findings indicate that gerunds are widely used as subjects, objects, or complements in both formal and informal contexts, while reported speech plays a key role in conveying indirect information in a formal and structured manner. However, several common errors were found, including incorrect tense shifts, pronoun usage, and sentence structure transformations. These findings imply the need for contextual and practice-oriented grammar instruction to help learners understand and apply these grammatical forms accurately across diverse communication settings.